CHITOSAN COMPOSITES PREPARED WITH HYDROXYAPATITE AND LACTIC ACID AS BONE SUBSTITUTE - Cardenas, Galo; Carrasco, Guido (Journal of the Chilean Chemical Society, 2019)
The need to find new therapies to improve the functioning of the injured tissue has made emerge a multidisciplinary field of research. Field that is related to the problems that exist for transplant to a patient with defect in their tissues and nerves, these trasplants are one of the most serious and costly health problems. In biomaterials research has undergone a major expansion, generating a variety of stands of different chemical nature. Biocompatible materials for human where they serve the same function as the actual tissues and also exhibit a total degradation in the body without the need for any other post-operation to remove a device installed on the bone region. Biodegradables and biocompatible composites prepared were subjected to studies to test the best concentrations of components of these, for example Chitosan(CH), hydroxyapatite(HAP) and polylactic acid(PLA), with these is created a material that fulfills the requirements for a good result in bone regeneration. The results showdifferent analyses of the composites that the proportion of Chitosan 4%, hydroxyapatite 3% and polylactic acid 1.5% is the more appropriate composition to produce a bone regeneration.